The Leading Transplantation Journals: A Trend Analysis, 2011–2021 - Badi Rawashdeh; Saif Aldeen Alryalat; Joohyun Kim; Calvin Eriksen; Mohammad Abu Assi; Raj Prasad; Matthew Cooper (Journal of Transplantation)
Background. As the field of transplantation has expanded, so have the quantity and variety of articles published on the topic. Evaluation of publications and journals is crucial to the expansion of transplant research. This study investigated the research output and journal metrics of the leading solid organ transplant journals published between 2011 and 2021 based on estimations of the trends in the category CiteScore from the Scopus database. Materials and Methods. We obtained data on the listed journals from the Scopus Source List. We then filtered the list for “Transplantation” journals. Only the top quartiles or quartile 1 (Q1) journals were placed in this category. This study focused specifically on transplantation journals and did not include other journals related to diseases of transplanted organs such as the kidney, liver, heart, and lungs. Results. The number of transplantation journals increased by 42.8% in the last ten years, from 28 in 2011 to 40 in 2021. Between 2011 and 2021, nine transplantation journals ranked in the highest quartile (Q1). The American Journal of Transplantation was the top journal in both years, with a 150% increase in citations and an 11.2% increase in articles published. Open access (OA) transplant journals rose from 3 in 2011 to 10 in 2021. In 2021, OA journals earned 8,555 citations, a 125% increase from 2011. Despite this increase, non-OA journals received more citations than OA in 2021 (p value 0.026). Conclusion. Solid organ transplantation advances lead to more publications and citations. Regular journals and publications evaluation benefits academics and policymakers by promoting the growth of research. This study examined solid organ transplantation journals and gave a global perspective on transplant journal rankings and compared their status in 2011 and 2021.